Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve this problem, we need to find the value of [tex]\(n\)[/tex] such that the arithmetic mean (AM) between [tex]\(a\)[/tex] and [tex]\(b\)[/tex] is equal to [tex]\(\frac{a^{n+1} + b^{n+1}}{a^n + b^n}\)[/tex].
The arithmetic mean of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] is given by:
[tex]\[ \text{AM} = \frac{a + b}{2} \][/tex]
According to the problem, this is equal to [tex]\(\frac{a^{n+1} + b^{n+1}}{a^n + b^n}\)[/tex]. Therefore, we set up the following equation:
[tex]\[ \frac{a + b}{2} = \frac{a^{n+1} + b^{n+1}}{a^n + b^n} \][/tex]
To eliminate the fractions, we cross-multiply:
[tex]\[ (a + b)(a^n + b^n) = 2(a^{n+1} + b^{n+1}) \][/tex]
Now, let's expand and simplify the left side:
[tex]\[ a^{n+1} + ab^n + ba^n + b^{n+1} = 2a^{n+1} + 2b^{n+1} \][/tex]
Rearranging all terms to one side gives:
[tex]\[ a^{n+1} + b a^n + a b^n + b^{n+1} - 2a^{n+1} - 2b^{n+1} = 0 \][/tex]
Grouping like terms, we get:
[tex]\[ -a^{n+1} + a b^n + b a^n - b^{n+1} = 0 \][/tex]
We can rewrite this as:
[tex]\[ a b^n + b a^n - a^{n+1} - b^{n+1} = 0 \][/tex]
Factor out common terms:
[tex]\[ a (b^n - a^n) + b (a^n - b^n) = 0 \][/tex]
Notice that [tex]\(b^n - a^n\)[/tex] and [tex]\(a^n - b^n\)[/tex] are opposites, so combining these terms gives:
[tex]\[ a b^n - a^{n+1} + b a^n - b^{n+1} = 0 \][/tex]
Which simplifies to:
[tex]\[ (ab^n - a^{n+1}) + (ba^n - b^{n+1}) = 0 \][/tex]
or:
[tex]\[ -a^{n+1} + a b^n + b a^n - b^{n+1} = 0 \][/tex]
Examining this expression, it must be true for all [tex]\(a\)[/tex] and [tex]\(b\)[/tex]. To satisfy the equation identically, consider the case where [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are equal. If we let [tex]\(a = b\)[/tex], then:
[tex]\[ a(a^n - a^n) + b(a^n - a^n) = 0 \][/tex]
This simplifies to:
[tex]\[ 0 = 0 \][/tex]
Independently of [tex]\(a\)[/tex] and [tex]\(b\)[/tex], this simplification holds valid. To find [tex]\(n\)[/tex], let's explore if a general [tex]\(n = 1\)[/tex] would simplify the problem. Substituting [tex]\(n = 1\)[/tex], let's check:
[tex]\[ \frac{a + b}{2} = \frac{a^{1+1} + b^{1+1}}{a^1 + b^1} = \frac{a^2 + b^2}{a + b} \][/tex]
This implies:
[tex]\[ \frac{a + b}{2} = \frac{a^2 + b^2}{a + b} \][/tex]
Multiplying both sides by [tex]\(a + b\)[/tex] leads to:
[tex]\[ a + b = \frac{a^2 + b^2}{a + b} \][/tex]
Thus, simplifying:
[tex]\[ a + b = \frac{a^2 + b^2}{a + b} \][/tex]
Upon rearrangement and ensuring the correctness:
[tex]\[ a + b = a + b \][/tex]
Therefore, the value of [tex]\(n\)[/tex] that satisfies this equation is indeed [tex]\( \boxed{1} \)[/tex].
The arithmetic mean of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] is given by:
[tex]\[ \text{AM} = \frac{a + b}{2} \][/tex]
According to the problem, this is equal to [tex]\(\frac{a^{n+1} + b^{n+1}}{a^n + b^n}\)[/tex]. Therefore, we set up the following equation:
[tex]\[ \frac{a + b}{2} = \frac{a^{n+1} + b^{n+1}}{a^n + b^n} \][/tex]
To eliminate the fractions, we cross-multiply:
[tex]\[ (a + b)(a^n + b^n) = 2(a^{n+1} + b^{n+1}) \][/tex]
Now, let's expand and simplify the left side:
[tex]\[ a^{n+1} + ab^n + ba^n + b^{n+1} = 2a^{n+1} + 2b^{n+1} \][/tex]
Rearranging all terms to one side gives:
[tex]\[ a^{n+1} + b a^n + a b^n + b^{n+1} - 2a^{n+1} - 2b^{n+1} = 0 \][/tex]
Grouping like terms, we get:
[tex]\[ -a^{n+1} + a b^n + b a^n - b^{n+1} = 0 \][/tex]
We can rewrite this as:
[tex]\[ a b^n + b a^n - a^{n+1} - b^{n+1} = 0 \][/tex]
Factor out common terms:
[tex]\[ a (b^n - a^n) + b (a^n - b^n) = 0 \][/tex]
Notice that [tex]\(b^n - a^n\)[/tex] and [tex]\(a^n - b^n\)[/tex] are opposites, so combining these terms gives:
[tex]\[ a b^n - a^{n+1} + b a^n - b^{n+1} = 0 \][/tex]
Which simplifies to:
[tex]\[ (ab^n - a^{n+1}) + (ba^n - b^{n+1}) = 0 \][/tex]
or:
[tex]\[ -a^{n+1} + a b^n + b a^n - b^{n+1} = 0 \][/tex]
Examining this expression, it must be true for all [tex]\(a\)[/tex] and [tex]\(b\)[/tex]. To satisfy the equation identically, consider the case where [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are equal. If we let [tex]\(a = b\)[/tex], then:
[tex]\[ a(a^n - a^n) + b(a^n - a^n) = 0 \][/tex]
This simplifies to:
[tex]\[ 0 = 0 \][/tex]
Independently of [tex]\(a\)[/tex] and [tex]\(b\)[/tex], this simplification holds valid. To find [tex]\(n\)[/tex], let's explore if a general [tex]\(n = 1\)[/tex] would simplify the problem. Substituting [tex]\(n = 1\)[/tex], let's check:
[tex]\[ \frac{a + b}{2} = \frac{a^{1+1} + b^{1+1}}{a^1 + b^1} = \frac{a^2 + b^2}{a + b} \][/tex]
This implies:
[tex]\[ \frac{a + b}{2} = \frac{a^2 + b^2}{a + b} \][/tex]
Multiplying both sides by [tex]\(a + b\)[/tex] leads to:
[tex]\[ a + b = \frac{a^2 + b^2}{a + b} \][/tex]
Thus, simplifying:
[tex]\[ a + b = \frac{a^2 + b^2}{a + b} \][/tex]
Upon rearrangement and ensuring the correctness:
[tex]\[ a + b = a + b \][/tex]
Therefore, the value of [tex]\(n\)[/tex] that satisfies this equation is indeed [tex]\( \boxed{1} \)[/tex].
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.